Activity patterns of birds in the central Free State, South Africa - Van Niekerk, Daniël Johan (University of the Free State, 2009)
Activity patterns of bird species were studied at Glen Agricultural College within the grassland area of the central Free State, South Africa, during a period of 11 years (July 1997 - July 2008). The study focused on a specific grassland locality where 5-minute checklists were compiled continuously from dawn to dusk at least once a week for a total of 656 days. Data were also collected each minute for selected species. Additional observations in an adjacent tree and shrub dominated drainage line included I-minute checklists compiled during transects over a two-year period (late autumn 2000/1 to mid-autumn 2002/3) as well as surveys from a fixed position from dawn to approximately 70 minutes after sunrise during 2007/8. The central aim of the study was to quantify and explain annual, seasonal and daily activity patterns of all bird species recorded in the study area. This data is summarised in separate species accounts where aspects of the annual cycle, particularly breeding and moulting, were also considered. In addition, the potential influence of rainfall was investigated. The study reveals, for the first time, how the activity patterns of a southern African bird community change through time, and how the amount and timing of rainfall can influence these patterns. In spite of similarities amongst species when daily, seasonal and annual patterns are considered separately, the study also shows that each species is unique when all its data is considered simultaneously. Because activity patterns can have a substantial influence on the detectability of a species, the accuracy and usefulness of surveys aimed at estimating bird numbers is consequently questioned. The study at Glen also shows how activity patterns can be used to help unravel the annual cycle of species in a time and cost effective way.
Thesis (Ph.D. (Zoology and Entomology))--University of the Free State, 2009
Keywords: Activity pattern; Annual cycle; Birds; Circadian rhythm; Circannual rhythm; Drainage line; Grassland; Rainfall; Birds -- Behavior -- South Africa -- Glen; Circadian rhythms; Larks -- South Africa -- Glen